Nonoperative Management of a Severe Proximal Rectus Femoris Musculotendinous Injury in a Recreational Athlete: A Case Report. Issue 12 (1st December 2018) - Park, C. Kevin; Zlomislic, Vinko; Du, Jiang; Huang, Brady K.; Chang, Eric Y.; Chang, Douglas G.
Abstract: This report describes a severe injury to the proximal rectus femoris (RF) muscle in a 37‐year‐old recreational athlete. This injury is a relatively rare occurrence in both the general and elite athletic populations. Acute and long‐term imaging and functional outcomes are described. This athlete was able to return to full activity without surgical intervention. Follow‐up imaging demonstrated gross healing of both complete (or near complete) muscle and tendon tears. Level of Evidence: V